Cover Image, Volume 113, Number 6, June 2016. Issue 6 (June 2016) - Velasco, Vanessa; Gruenthal, Mark; Zusstone, Esther; Thomas, Jonathan M. D.; Berson, R. Eric; Keynton, Robert S.; Williams, Stuart J.
Abstract : Cover Legend This figure is the top view of the orbital‐shear impedance chip. Its design incorporated three arrays of 200 μm diameter sensing electrodes (small dark gray circles of inset image) and neighboring counter electrode strips. Three additional counter electrodes (large dark gray circles) were included to determine the influence of counter electrode proximity to sensing electrodes. Contact pads (bottom row) were patterned to fit into a commercial card reader. The dashed blue line indicates the perimeter of the PDMS well containing the endothelial cell monolayer. The cover image, by Stuart J. Williams et al., is based on the Article An orbital shear platform for real‐time, in vitro endothelium characterization, DOI:10.1002/bit.25893 .